Desarrollo de una aplicación para el cálculo de cargas térmicas para aire acondicionado. - Toledo Granda, Kliover Omar (2015)
This project allows the calculation of thermic loads during a program that took place in macros VBA, (visual Basic for Application), which is the language of programming that is used for the creation of the macros Excel. This program VBA allows the calculation of thermic loads of a space, following the ASHRAE method CLTD/CLF (Cooling Load Temperature Difference and Cooling Load Factor). With the climate conditions of Loja province, Guayas, Imbabura, Pichincha, Esmeraldas, Manabí, Napo, El Oro, Cañar, Tungurahua. The tool used allows a high grade of precision and features with all necessary data for calculating thermic loads of exterior walls, roofs, glass and thermic loads of internal lighting, people, equipment infiltration and ventilation. The parts of which this work consists are sufficient. To be able to perform calculations of thermic loads for buildings and all existing variables in one of these calculations. With the present program was achieved to expedite the calculation for system of air conditioned and hence select equipment to be installed.